(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Although conventional phaco and femtosecond laser-assisted cataract surgery are widely used treatment options, patients undergoing these approaches often experience peri- and post-operative complications that worsen functional outcomes. Cystic macular edema is one of these complications and occurs in 1-28% of patients. Purpose: To assess the efficacy of surgical treatment for age-related cataract through risk factor analysis using logistic regression models. Materials and Methods: Eighty-three eyes of 83 patients with age-related cataract (lens nuclei of grades 1 to 3, Buratto classification scheme) participated in the study. Aqueous humor samples were collected during phacoemulsification procedures and investigated for the presence of prostanoids, thromboxane B2 and prostacyclin 6-keto-PGF1α. A negative outcome of surgical treatment for cataract was defined as development of macular edema; any other outcome was considered positive. Results: 6-keto-PGF1α/ thromboxane B2 ratio can be used as a marker of the risk for developing macular edema 1 year after phacoemulsification for age-related cataract.